Pertumbuhan dan Hasil Tanaman Kacang Hijau (Vigna radiata L.) Akibat Pengaruh Pemberian Pupuk Organik Kotoran Sapi - I Made Sukerta; I Ketut Sumantra; Anak Agung Abi Laksamana (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2024)
The purpose of this study was to determine the effect of applying Cow Manure Organic Fertilizer on the growth and yield of green bean plants and determine the dose of cow dung organic fertilizer with the best results. This study was conducted for 2 months starting from December 18, 2022 to February 25, 2023. The method used in this study used a randomized block design (RBD) with six (6) treatments, repeated four times (4), so there were 24 polybags. The treatment used was no organic fertilizer, (P0) = no organic cow manure (25 g/polybag), (p2) = 10 tons/ha organic cow manure (50 g/polybag), (p3) = 15 tons/ ha organic cow manure (75 g/polybag), (p4) = 20 tonnes/ha organic cow manure (100 g/polybag), (p5)= 25 tonnes/ha organic cow manure (125 g/polybag). The results showed that the organic fertilizer treatment of cow dung had a very significant effect on all observed parameters. The application of several types of organic fertilizers has a very significant effect on the parameters of plant height, number of plant leaves, number of branches, leaf area, number of pods, number of filled pods, seed fresh weight, fresh case weight, oven dry weight of seeds oven dry weight and the best dose. Cow dung organic fertilizer which influences the growth and yield of mung bean (Vigna radianta L.) is the treatment of 15 tonnes/ha (75g/polybag) and the yield of seed fresh weight (15.12 g) and seed oven dry weight (8, 59g).